Effect of pressure on the magnetic properties of CrB2 - Grechnev, G.E.; Panfilov, A.S.; Fedorchenko, A.V.; Filippov, V.B.; Lyashchenko, A.B.; Vasiliev, A.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
Magnetic susceptibility c of the itinerant antiferromagnet CrB2 with TN ≃ 87K was studied as a function of the hydrostatic pressure up to 2 kbar at fixed temperatures 78 and 300 K. The pressure effect on c is found to be negative in sign and weakly dependent on the magnetic state of the compound. In addition, the measured pressure dependence of the Néel temperature, dTN / dP = (0.1 ± 0.1) K/kbar, is roughly two orders of magnitude smaller than the corresponding value for the pure chromium. The main contributions to c andtheir volume dependence are calculated ab initio within the local spin density approximation, and appearedto be in close agreement with the experimental data.